Evaluation of the Impact of Consciousness Energy Healing Treatment on the Isotopic Abundance Ratios (PM+1/PM and PM+2/PM) of Ofloxacin - Trivedi, Dahryn; Kumar Trivedi, Mahendra; Branton, Alice; Nayak, Gopal; Jana, Snehasis (Journal of New Developments in Chemistry, 2019)
Ofloxacin is a class of fluorinated quinolone antibiotics, useful against most of the Gram-positive and Gram-negative bacterial infections. This study was designed to investigate the impact of the Trivedi Effect®-Consciousness Energy Healing Treatment on the structural properties and the isotopic abundance ratio of ofloxacin using LC-MS and GC-MS spectroscopy. Ofloxacin sample was divided into control and treated parts. The control ofloxacin did not receive the Consciousness Energy Healing Treatment, while the treated ofloxacin receives the Consciousness Energy Healing Treatment remotely by a renowned Biofield Energy Healer, Dahryn Trivedi. The LC-ESI-MS spectra of both the samples of ofloxacin at the retention time 3.05 minutes exhibited the mass of the protonated molecular ion peak at m/z 362.17 (M+H)+ (calculated for C18H21FN3O4+, 362.15). The LC-MS based isotopic abundance ratio of PM+1/PM in the treated ofloxacin was significantly increased by 56.57% compared with the control sample. Thus, 2H, 15N, 13C, and 17O contributions from (C18H21FN3O4)+ to m/z 363.17 in the treated ofloxacin were considerably increased compared with the control sample. The GC-MS based isotopic abundance ratios of PM+1/PM and PM+2/PM in the treated ofloxacin was significantly increased by 9.53% and 12.94%, respectively compared with the control sample. Hence, 2H, 15N, 13C, 17O, and 18O contributions from (C18H21FN3O4)+ to m/z 318 and 319 in the treated ofloxacin were significantly increased compared with the control sample. The LC-MS and GC-MS based isotopic abundance ratios of PM+1/PM (2H/1H or 15N/14N or 13C/12C or 17O/16O), and PM+2/PM (18O/16O) in the treated ofloxacin were considerably improved compared to the control sample. The increased isotopic abundance ratio of the treated ofloxacin would increase the chemical bond strength and increase the stability in the body. The new form of treated ofloxacin would be more stable compared to the control sample and would be very useful to design improved pharmaceutical formulations that might offer better therapeutic response against infections of the urethra and cervix, infectious diarrhoea, urinary tract infections, cellulitis, chronic bronchitis, pneumonia, prostatitis, multidrug-resistant tuberculosis, plague, otitis media, etc.
Keywords: Ofloxacin; Consciousness Energy Healing Treatment; The Trivedi Effect; Isotopic Abundance Ratio; Quinolone Antibiotics